2022
DOI: 10.3897/mycokeys.92.87593
|View full text |Cite|
|
Sign up to set email alerts
|

New studies on Apiospora (Amphisphaeriales, Apiosporaceae): epitypification of Sphaeria apiospora, proposal of Ap. marianiae sp. nov. and description of the asexual morph of Ap. sichuanensis

Abstract: In the present work, an epitype for Sphaeria apiospora, the basionym of the type species of the genus Apiospora, Apiospora montagnei, is selected among collections growing in the host plant species reported in the original protologue, Arundo micrantha. Most samples obtained from localities near that of the lectotype (Perpignan, France) belong to the same species, which is not significantly different from the clade previously named Ap. phragmitis, suggesting that this name is a later synonym of Ap. montagnei. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
3
9
1
Order By: Relevance
“… hainanensis clustered together with significant support in an isolated branch basal to A. sacchari and related species of the phaeospermum clade ( Pintos and Alvarado 2022 ; Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… hainanensis clustered together with significant support in an isolated branch basal to A. sacchari and related species of the phaeospermum clade ( Pintos and Alvarado 2022 ; Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…An epitype for the type species of Apiospora , A. montagnei , was recently proposed by Pintos and Alvarado (2022) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, the Apiospora genus was phylogenetically placed in the same phylogenetic clade as Arthrinium (Crous and Groenewald 2013 ; Wang et al 2018 ). Recently, studies have shown a phylogenetic delimitation of the Apiospora genus and the Arthrinium genus (Crous et al 2021 ; Pintos and Alvarado 2021 , 2022 ; Tian et al 2021 ; Sørensen et al 2022 ). The genus Apiospora comprises species that occur in a wide variety of geographic and ecological environments.…”
Section: Introductionmentioning
confidence: 99%
“…With the availability of sequence data of A. montagnei , Pintos and Alvarado (2022) revealed that Apiospora and Arthrinium are distinct genera. With most Apiospora species sharing similar morphologies, molecular phylogenetic information is necessary for accurate species identification ( Pintos and Alvarado 2022 ).…”
Section: Introductionmentioning
confidence: 99%